QUALITY OF LIFE OF PATIENTS UNDERGOING ONCOLOGY TREATMENT IN THE CITY OF PALOTINA PR (REMUNOM, 2024)
Exploratory study that aimed to evaluate the quality of life of patients undergoing cancer treatment. This was an exploratory, quantitative study, carried out with patients undergoing oncological treatment, from September to November 2023, in the city of Palotina/Pr. Data were collected using a semi-structured questionnaire divided into two parts; sociodemographic and clinical characterization. The results of the study show changes in women regarding mood (36.6%), incidence of pain (26.7%), feeling of fatigue (19.2%), and insomnia (17.10%). In male patients, the biggest impacts are on mood changes (29.9%), insomnia (25%), feelings of fatigue (23.8) and pain (16%).In this study it was proven that the percentage of changes in mood, pain, feelings of fatigue and insomnia in patients who practice physical activity is lower and, parallel to this, the incidence of non-practitioners of physical activity is high. Therefore, it is necessary to expand physical activity incentive programs, as well as multidisciplinary intervention projects, aimed at controlling such complications.